Investigations into the antibacterial effects and potential mechanism of gambogic acid and neogambogic acid - Li, Mingzhu; Chen, Yuan; Wang, Lijuan; Lu, Chujie; Chen, Peiying; Jin, Yuanling; Li, Jiacong; Gao, Fei; Shang, Zhuo; Lin, Wei (Frontiers in Microbiology, 2022)
The growing threat of antibiotic-resistant bacterial infections to public health necessitates the development of novel antibacterial agents. Inhibiting bacterial cell wall synthesis has remained a key focus for antibiotic development. Our search for inhibitors of undecaprenyl diphosphate synthase (UPPS), an essential enzyme required for bacterial cell wall formation, revealed that two primary components of gamboge, gambogic acid (GA) and neogambogic acid (NGA), significantly inhibited the activity of Enterococcus faecalis UPPS (EfaUPPS) with the half maximal inhibitory concentrations (IC50) of 3.08 μM and 3.07 μM, respectively. In the in vitro antibacterial assay, both GA and NGA also exhibited inhibitory activities against E. faecalis with the minimal inhibitory concentrations (MICs) of 2 μg/mL. Using microscale thermophoresis, molecular docking, and enzymatic assays, we further confirmed that GA and NGA occupy the substrate binding pocket of EfaUPPS with micro-molar binding affinity, preventing the natural substrates farnesyl diphosphate (FPP) from entering. Mutagenesis analysis revealed that L91 and L146 are two key residues in the binding between GA/NGA and UPPS. Furthermore, we also demonstrated that GA and NGA can improve E. faecalis-induced undesirable inflammation in a mouse infection model. Taken together, our findings provide a basis for structural optimization of GA/NGA to develop improved antibiotic leads and enhance treatment success rates in clinical practice.